Critical Discourse Analysis the Lyrics of the Song "Runtuh" by Feby Putri Feat Fiersa Besari Van Djik's Theory - Siti Rohmatul Ummah; Supryanti; Khusnul Irma; Sri Utami (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aims to analyze the lyrics of the song Runtuh by Feby Putri featuring Fiersa Besari using Teun A. Van Dijk’s Critical Discourse Analysis (CDA). This research employs a qualitative descriptive method with a linguistic approach. The primary data consist of the official lyrics of Runtuh, while secondary data are collected from books, scholarly journal articles, and relevant online sources discussing discourse analysis, song lyrics, and Van Dijk’s theory. The analysis is conducted through Van Dijk’s three dimensions: text structure (macrostructure, superstructure, and microstructure), social cognition, and social context. The findings reveal that the song represents emotional exhaustion, vulnerability, self-acceptance, and the struggle to let go of painful experiences. The lyrics also criticize social expectations that encourage individuals to suppress negative emotions and maintain an image of happiness despite inner suffering. Furthermore, the song reflects contemporary social issues, particularly emotional suppression and toxic positivity, while promoting empathy, emotional honesty, and self-acceptance. Overall, Runtuh functions not only as a medium of emotional expression but also as a form of social criticism toward the pressures experienced by individuals in modern society.